ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIK SISWA SMP DI KABUPATEN BANDUNG BARAT PADA MATERI SEGIEMPAT DAN SEGITIGA - Hanifah, Hanifah; Nurjaman, Adi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
Thinking creative is a thinking process which to produce kinds of idea possibility and the way widely and many to completed a problem, when applied thinking creative, will produce many useful ideas to find the resolver. Creative connects with finding something, about the thing that produces something new with using something that has been there. Research methods will use is descriptive qualitative. As for the sample in this research are seventh grade with high ability, medium and low in Kabupaten Bandung Barat. For the instrument test thinking, the creative ability will deliver to students are five question and following with interview in each student. Then, the results obtained was the level of their thinking creative ability according to their writing test and results of the interview with the low-level students. Next, this research is parts of my research paper will be careful.